Checklist of the nematode parasites of wild birds of Argentina - Drago, Fabiana Beatriz (2020)
A commented checklist of the nematodes parasites of Argentinean wild birds is presented. This is the first compilation of parasitological papers about nematodes of Argentinean birds published between 1873 and November 2019. This review includes information about 64 nematode nominal species and 13 taxa identified at generic level, belonging to five orders, 16 superfamilies, 20 families, and 44 genera. Five species were considered incertae sedis, because they were described based only on larval stages, and one species was maintained as species inquirenda. The highest number of taxa of nematodes was recorded in the family Acuariidae with 20 nominal species and two taxa identified at generic level, followed by Anisakidae with eight nominal species and one taxon identified at generic level, and Tetrameridae with eight nominal species and two taxa identified at generic level. Of the 1042 species of birds reported in Argentina, only 65 (6.24%) were reported as hosts of adult nematodes. The families of birds with the highest number of reported taxa were Tinamidae (12 nematode taxa), Laridae (11), Anatidae (8) and Phalacrocoracidae (7). The present review provides data on hosts, geographical distribution, sites of infection, location of material deposited in Helminthological Collections, references, and taxonomic comments. A host/parasite list is also provided.